Single Cell Analysis of the Fate of Injected Oncogenic RasV12 Cells in Adult Wild Type Drosophila - Di Chen; Xiao Lan; Xiaoming Huang; Jieqing Huang; Xiaojing Zhou; Zhichao Miao; Yuting Ma; Akira Goto; Shanming Ji; Jules A. Hoffmann (Karger Publishers, 2023)
We have injected dish-cultured oncogenic RasV12 cells into adult male flies and analyzed by single cell transcriptomics their destiny within the host after 11 days. We identified in the preinjection samples and in the 11-day postinjection samples in all 16 clusters of cells, of which 5 disappeared during the experiment in the host. The other cell clusters expanded and expressed genes involved in the regulation of cell cycle, metabolism, and development. In addition, three clusters expressed genes related to inflammation and defense. Predominant among these were genes coding for phagocytosis and/or characteristic for plasmatocytes (the fly equivalent of macrophages). A pilot experiment indicated that the injection into flies of oncogenic cells, in which two of most strongly expressed genes had been previously silenced by RNA interference, into flies resulted in a dramatic reduction of their proliferation in the host flies as compared to controls. As we have shown earlier, the proliferation of the injected oncogenic cells in the adult flies is a hallmark of the disease and induces a wave of transcriptions in the experimental flies. We hypothesize that this results from a bitter dialogue between the injected cells and the host, while the experiments presented here should contribute to deciphering this dialogue.